2015
DOI: 10.1007/s11606-015-3517-x
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Technology to Engage and Communicate with Patients: A Survey of Patient Attitudes

Abstract: BACKGROUND: As primary care moves toward a system of population health management, providers will need to engage patients outside traditional office-based interactions. OBJECTIVE: We assessed patient attitudes regarding technology use to communicate with their primary care team or to engage with other patients outside typical office settings. Design/Participants/Main Measures We c o n d u c t e d a n a t i o n a l s u r v e y u s i n g G f K KnowledgePanel ® to examine attitudes on the use of digital technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…This appears important for the measurement of attitudes toward health-related topics because attitudes are typically assumed to be located within a unidimensional continuum, that is, positive or negative attitudes, but not both for the same object [34]. In recent years, attitudes toward e-mental health treatments have been mainly investigated among patients [35-37] and health care professionals [38-40]. For instance, the “Attitudes towards Psychological Online Interventions Questionnaire” (APOI) [36] is a validated measure with depressive patients in a German clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…This appears important for the measurement of attitudes toward health-related topics because attitudes are typically assumed to be located within a unidimensional continuum, that is, positive or negative attitudes, but not both for the same object [34]. In recent years, attitudes toward e-mental health treatments have been mainly investigated among patients [35-37] and health care professionals [38-40]. For instance, the “Attitudes towards Psychological Online Interventions Questionnaire” (APOI) [36] is a validated measure with depressive patients in a German clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jenssen et al27 showed that more patients preferred to use e-mail or face-to-face communicating with the GP about their health and health care rather than using social media or text messaging.…”
Section: Discussionmentioning
confidence: 99%
“…Text-messaging and phone-based video calls (like Facetime™ and Snapchat™) are not secure, nor can they be easily copied into a chart for documentation of a patient encounter, and so can not be incorporated into the options for communication at this time. Some studies have demonstrated that patients tend to be most comfortable with email for communicating with health care personnel: the youngest, those who have more health literacy and more education, tend to prefer secure email (Huan et al 2015, Jenssen et al 2016. Technology continues to evolve to meet the needs of consumers, and secure methods available for patient-provider communication will likely expand to provide more options over time.…”
Section: Telehealthmentioning
confidence: 99%